Can the descriptive-substantive link survive beyond democracy? The policy impact of women representatives. Issue 8 (17th November 2019) - Forman-Rabinovici, Aliza; Sommer, Udi
ABSTRACT: That women offer substantive representation in democratic systems is well established. However, can they do so in partial or non-democracies? As less than half of the women in the world live in democracies, analysing female representation outside of the democratic context is crucial. We hypothesize that even in non- and partial-democracies, women exercise substantive representation. Neutralizing the confounding effects of international constraints or a general positive approach towards gender equality, we create a framework that observes the relationship, proposing and testing several scenarios to identify substantive representation. We observe correlations over time between the share of women representatives and policies female representation typically influence: reproductive rights, health spending and education spending. Our evidence shows that substantive representation appears in non- and partial democracies, and not just in democracies.